Implementing screening for hypertension in archetypal HIV primary care: a mixed-methods assessment - Lydia Buzaalirwa; Lydia Nambala; Grace Banturaki; Penninah Iutung Amor; Anne Katahoire; Elvin Geng; Aggrey Semeere (BMC, 2022)
Abstract Background High prevalence of HIV and hypertension in sub-Saharan Africa puts adults living with HIV (ALWH) at high risk of end-organ complications. Both World Health Organization (WHO) and national guidelines recommend screening and treatment of hypertension among ALWH on antiretroviral therapy (ART). We evaluated the implementation of hypertension screening among adults on ART at three Uganda Cares Primary care facilities. Methods Using a sequential explanatory mixed-methods approach, we reviewed patient records, and interviewed both patients and providers during 2018 and 2019. We obtained demographics, clinical and blood pressure (BP) measurements via records review. We estimate the period prevalence of screening and use adjusted modified Poisson regression models to evaluate predictors of screening. In-depth interviews were analysed using a thematic approach to explain the observed prevalence and predictors of BP screening. Results Records for 1426 ALWH were reviewed. Patients had a median age of 35 years and 65% of them were female. Most were on ART (89% on first-line) with a median duration of 4 years. Only 262 (18%) were overweight or obese with a body mass index (BMI) > 25 Kg/M2. In 2017 or 2018 patients made a median of 3 visits and 783 patients had a BP recorded, hence a period prevalence 55%. Older age, male sex, more clinic visits, and clinic site were associated with screening in the adjusted analyses. Erratic BP screening was corroborated by patients' and providers' interviews. Challenges included; high patient numbers, low staffing, provider apathy, no access to treatment, and lack of functioning of BP equipment. Conclusion Almost half of regular HIV clinic attendees at these prototypical primary care HIV clinics were not screened for hypertension for a whole year. Improving BP screening requires attention to address modifiable challenges and ensure local buy-in beyond just providing equipment.